Impact of the severity of obstructive sleep apnea-hypopnea syndrome on the quality of life and exercise tolerance in hypertensive patients - Stojanović, Milovan; Deljanin Ilić, Marina; Ristić, Lidija; Stamenković, Zoran; Koraćević, Goran; Petrović, Dejan; Gojković, Dejana; Kostić, Jovana (Vojnosanitetski pregled, 2026)
Background/Aim. Obstructive sleep apnea-hypopnea syndrome (OSAHS) is associated with impaired quality of life (QoL) and reduced exercise tolerance. The aim of the study was to determine whether the severity of OSAHS influences the QoL and exercise tolerance in patients with moderate to severe OSAHS and arterial hypertension. Methods. The study included 115 consecutive patients with arterial hypertension and either moderate [40 (34.78%)] or severe [75 (65.22%)] OSAHS. Exercise tolerance was assessed using the exercise stress test, while QoL was evaluated with the Short Form-36 (SF-36) questionnaire. Results. The groups under study did not differ significantly in terms of age (54.80 ± 8.91 vs. 53.55 ± 9.53, p = 0.494) or sex distribution [females: 11 (27.50%) vs. 13 (17.33%), p = 0.201]. A high prevalence of cardiovascular risk factors was observed in the study population. Patients with severe OSAHS had significantly higher body mass index and neck circumference. Obesity was also more frequent among patients with severe OSAHS. In addition, this group demonstrated significantly higher apnea-hypopnea index, desaturation index, and time spent with oxygen saturation below 90%. There were no statistically significant differences in either exercise tolerance or the SF-36 parameters between the groups. Furthermore, no significant correlations were observed between apnea-hypopnea index, exercise tolerance, and QoL parameters. Multivessel coronary artery disease was detected in two asymptomatic patients. Conclusion. Patients with OSAHS overall exhibit multiple cardiovascular risk factors and are characterized by reduced QoL and decreased exercise tolerance. No significant correlation was found between OSAHS severity and exercise tolerance and QoL. The detection of multivessel coronary artery disease in asymptomatic patients in the study underscores the clinical significance of screening for coronary heart disease in patients diagnosed with OSAHS.